2012
DOI: 10.5539/ijbm.v7n10p49
|View full text |Cite
|
Sign up to set email alerts
|

AHP Approach for Supplier Evaluation and Selection in a Pharmaceutical Manufacturing Firm in Ghana

Abstract: In today's highly competitive environment, improper evaluation and selection of the right suppliers can hinder an organizations supply chain performance. The aim of this study is to present a suitable methodology for the evaluation and selection of suppliers in a pharmaceutical manufacturing firm in Ghana. Specifically, the study sought to use the Analytic Hierarchy Process methodology to select the most appropriate raw material suppliers of the artemether-lumefantrine anti-malarial drug for the case study org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 14 publications
0
37
0
8
Order By: Relevance
“…1, starting from formulating Direct Answer Matrix, Original Average Matrix, Normalizing the Direct Influence Matrix, Deriving the Total Relation Matrix and deciding threshold value to get the CER diagram [18]. Step -1 Gather DMs opinion and formulate the Direct Answer Matrix 'A'…”
Section: Application Of Dematel Methodmentioning
confidence: 99%
“…1, starting from formulating Direct Answer Matrix, Original Average Matrix, Normalizing the Direct Influence Matrix, Deriving the Total Relation Matrix and deciding threshold value to get the CER diagram [18]. Step -1 Gather DMs opinion and formulate the Direct Answer Matrix 'A'…”
Section: Application Of Dematel Methodmentioning
confidence: 99%
“…It proposes a fuzzy analytic HierarchyProcess (Fuzzy-AHP) to consider and handle efficiently based on both types of criteria in the selection of global supplier in pharmaceutical industry. Asamoah et al (2012),in a study observed that the AHP makes it easier to evaluate, rank and select efficient supplier for pharmaceutical manufacturing firms in a timely and reliable manner. Mainly three criteria -quality, price, and reliability/capacity were chosen to select most efficient supplier.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most researchers are following technical parameters issues in supplier selection process (Tidwell & Sutterfield, 2012;Chandra & Grabis, 2003;Pearson & Ellram, 1995). Researchers have been using different techniques from mixed integer programming and multi-objective programming (Stadtler, 2007;Weber & Ellram, 1993) to application of the AHP/ANP and Fuzzy theory for supplier selection (Kahraman et al, 2003;Asamoah et al, 2012). Accounting for relations and inner relations between the criteria as well as the objectives makes the ANP-QFD more realistic and more reliable for the selecting process (Ordoobadi, 2012).…”
Section: Supplier Selectionmentioning
confidence: 99%